Test, test, test – a complication of testing for coronavirus disease 2019 with nasal swabs. Issue 7 (28th July 2020) - Mughal, Z; Luff, E; Okonkwo, O; Hall, C E J
Abstract: Background: Coronavirus disease 2019, a highly transmissible respiratory infection, has created a public health crisis of global magnitude. The mainstay of diagnostic testing for coronavirus disease 2019 is molecular polymerase chain reaction testing of a respiratory specimen, obtained with a viral swab. As the incidence of new cases of coronavirus disease 2019 increases exponentially, the use of viral swabs to collect nasopharyngeal specimens is anticipated to increase drastically. Case report: This paper draws attention to a complication of viral swab testing in the nasopharynx and describes the premature engagement of a viral swab breakpoint, resulting in impaction in the nasal cavity. Conclusion: This case highlights a possible design flaw of the viral swab when used to collect nasopharyngeal specimens, which then requires an aerosol-generating procedure in a high-risk patient to be performed. The paper outlines a safe technique of nasal foreign body removal in a suspected coronavirus disease 2019 patient and suggests alternative testing materials.